Предмет: Алгебра,
автор: dimadm
(8b-8)(8b+8)-8b(8b+8) его значение при b=2,6
Ответы
Автор ответа:
0
64b² - 64 - 64b² - 64b = - 64 - 64b,
Пусть b = 2,6 , тогда - 64 - 166,4 = - 230,4.
Ответ: - 230,4
Пусть b = 2,6 , тогда - 64 - 166,4 = - 230,4.
Ответ: - 230,4
Автор ответа:
0
(8b-8)(8b+8)- 8b(8b+8) =
=64b²-64 -64b²-64b =
=-64b-64 = -64 *(b+1)
при b=2.6
-64 * (2.6+1) = -64 *3.6=-230.4
проверим на полном выражении:
(8*2,6-8)(8*2,6+8) - 8*2,6*(8*2,6+8)=
=(8*2,6+8) * (8*2,6-8+8*2,6) =
= (8*2,6+8) * (-8) =
=28,8 *(-8)=-230,4
=64b²-64 -64b²-64b =
=-64b-64 = -64 *(b+1)
при b=2.6
-64 * (2.6+1) = -64 *3.6=-230.4
проверим на полном выражении:
(8*2,6-8)(8*2,6+8) - 8*2,6*(8*2,6+8)=
=(8*2,6+8) * (8*2,6-8+8*2,6) =
= (8*2,6+8) * (-8) =
=28,8 *(-8)=-230,4
Похожие вопросы
Предмет: Русский язык,
автор: mozhaevae07
Предмет: Английский язык,
автор: Аноним
Предмет: Математика,
автор: irassaa
Предмет: Биология,
автор: nastia1399iua
Предмет: Химия,
автор: Nurzii